Stosowanie przepisów Kodeksu postępowania administracyjnego o milczącym załatwieniu sprawy - Gajda-Durlik, Małgorzata (Studia Prawa Publicznego, 2018)
The subject of the considerations is the issue of the scope of the Code of Administrative Procedure in matters for which an institution of silent settlement is provided in separate provisions. The matter outlined above is the source of controversy which arises from the mechanism of anchoring to the framework of the Code of Administrative Procedure the institution of silent settlement under the act by the Act of 7 April 2017 amending the Act – Code of Administrative Procedure and certain other acts. It should be emphasised that the idea underlying the inclusion of the Code of this legal institution in the subject of regulation was to ensure proper effectiveness of the application of law by administrative means, to significantly reduce the social costs of launching the procedure and to deformalise as much as possible the activities undertaken in the official mode. The source of the concept was also the need to organise and comprehensively regulate the matter of individual administrative matters settled in a silent manner, which until now, functioned in substantive administrative law in a dispersed manner, with a diversified specificity of legal solutions. The measure of such a codification process was to be the formation of a uniform and clear procedural regime in the field of administrative law relations, expressed in the forms of silent settlement of a matter, on the one hand based on the formula of limiting formal requirements to the minimum necessary, and on the other hand corresponding to the features of the jurisdictional process with guarantees of protection of individual rights and the rule of law. However, the question arises whether such boundary conditions are fulfilled by the model of fusion with the Code of Administrative Procedure of the institution of silent settlement of the matter. For the practice of applying the law with the use of the institution, rooted already in the acts of the substantive law of the institution, there is a special significance in terms of reference to the procedural constructions of Chapter 8a of the Administrative Procedure Code. The issue of fundamental importance for defining the role of the act in the field of connecting the institution of silent settlement of a matter with the Code is not only the objective separation of the sphere of influence of unified formal and legal solutions of this act, but also defining the manner of merging procedural issues of the institution with the Code.